Status and Role of Manganese in the Environment - Kamble, RK; Thakare, MG (International Journal of Environment, 2014)
Manganese is the second most abundant heavy metal, and in frequency list of elements it occupies 12th place. The Earth’s core contains about 1.5% manganese. According to Indian Standards for Drinking water (IS 10500:2012) manganese concentration in drinking water is 0.1 ppm (acceptable limit) and 0.3 ppm as permissible limit. An attempt has been made to record the presence of manganese in different environmental matrices such as air, water, soil, food, its effects on plants, animals including human beings. DOI: http://dx.doi.org/10.3126/ije.v3i3.11081 International Journal of Environment Vol.3(3) 2014: 222-234